EFEKTIFITAS KEBIJAKAN PENCEGAHAN PENURUNAN ANGKA STUNTING DI PROVINSI SUMATERA BARAT - Suryanti, Rini; Hayati, Nandie (Ensiklopedia of Journal, 2024)
Stunting is a problem that is increasingly being found in developing countries, including Indonesia. The stunting prevention program is a national development program which is included in health development. Because growth at an early age is very important to pay attention to, including the prevalence of poor nutrition and the prevalence of sensitive nutrition. Regulations serve as a reference for government programs to see whether or not a region is effectively implementing a program, namely the program to reduce stunting rates. This research was carried out using a literature study, much of which data was obtained from books, journals and laws and data classification was obtained using qualitative research and a descriptive approach to the results obtained. This research aims to see the effectiveness of reducing stunting rates in implementing government programs. From the research results it was revealed that the program created by the government as outlined in Presidential Regulation number 72 of 2021 Article 1 paragraph 1 concerning the acceleration of stunting reduction, has not been able to reduce the existing stunting rate. in every region in West Sumatra province. This is caused by the implementation of the stunting reduction program still focusing on one stakeholder, namely the Health Service in each region in West Sumatra. In fact, stunting interventions focus more on sensitive nutrition, which should ideally be carried out through various development activities outside the health sector which will contribute to 70% of stunting interventions. Keywords: Effectiveness, Policy, Prevention, Reduction, Stunting